Standardization, Comercialization and Productivity on Doormat Creativity Industries Competitiveness - Prasetyo, P Eko (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
In the era of industrial revolution 4.0, industrial products are required to be able to have good product standards and productivity, so that the commercialization of industrial products is more adaptable and accepted by the market. If industrial products do not have standardization and good productivity, then industrial products will not be able to compete in the domestic market and global markets. The purpose of this research is to describe the influence of standardization, commercialization and productivity on the competitiveness of creative industries. This paper used quantitative descriptive research employs a path analysis. The main source of data used is primary fundamental microeconomic data, with 125 units of doormat creative home industry surveyed through simple random sampling as its respondents. The research results show that there is relatively strong and significant correlation and positive and significant influence between standardization, commercialization and productivity on the industrial competitiveness, either partially or jointly. Productivity is the biggest contributor to total correlation and influence to enhance industrial competitiveness.